2019
DOI: 10.1155/2019/1742341
|View full text |Cite
|
Sign up to set email alerts
|

Based on Integrated Bioinformatics Analysis Identification of Biomarkers in Hepatocellular Carcinoma Patients from Different Regions

Abstract: Accumulating statistics have shown that liver cancer causes the second highest mortality rate of cancer-related deaths worldwide, of which 80% is hepatocellular carcinoma (HCC). Given the underlying molecular mechanism of HCC pathology is not fully understood yet, identification of reliable predictive biomarkers is more applicable to improve patients' outcomes. The results of principal component analysis (PCA) showed that the grouped data from 1557 samples in Gene Expression Omnibus (GEO) came from different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“… 164 A growing number of studies have screened critical genes in HCC as potential biomarkers through bioinformatics assessments. 165 , 166 , 167 A number of hub genes were targeted from protein–protein interaction networks (PPIs) of differentially express genes (DEGs), which were filtered using software from online databases. For instance, integrated bioinformatics analysis derived from 927 HCC tissues and 630 adjacent normal tissues in the Gene Expression Omnibus (GEO) database detected several core genes closely associated to functional pathways involved in the carcinogenesis and progression of HCC, including FOXM1, CCNA2, AURKA, CDKN3, CDC20 and FTCD.…”
Section: Protein Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“… 164 A growing number of studies have screened critical genes in HCC as potential biomarkers through bioinformatics assessments. 165 , 166 , 167 A number of hub genes were targeted from protein–protein interaction networks (PPIs) of differentially express genes (DEGs), which were filtered using software from online databases. For instance, integrated bioinformatics analysis derived from 927 HCC tissues and 630 adjacent normal tissues in the Gene Expression Omnibus (GEO) database detected several core genes closely associated to functional pathways involved in the carcinogenesis and progression of HCC, including FOXM1, CCNA2, AURKA, CDKN3, CDC20 and FTCD.…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…For instance, integrated bioinformatics analysis derived from 927 HCC tissues and 630 adjacent normal tissues in the Gene Expression Omnibus (GEO) database detected several core genes closely associated to functional pathways involved in the carcinogenesis and progression of HCC, including FOXM1, CCNA2, AURKA, CDKN3, CDC20 and FTCD. 165 …”
Section: Protein Biomarkersmentioning
confidence: 99%
“…International Publisher diagnosed at an advanced stage [3]. Currently, serum alpha-fetoprotein (AFP) levels combined with computed tomography (CT) and magnetic resonance imaging (MRI) are the most common non-invasive diagnostic methods, but all of them have sensitivity problems [9].…”
Section: Ivyspringmentioning
confidence: 99%
“…The mortality of Liver cancer ranks second among human cancers worldwide [1,2]. It is reported that hepatocellular carcinoma (HCC) occupy approximately 80% of liver cancers [3]. In 2018, about 840,000 HCC patients were newly diagnosed and 782,451 deaths were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Principal component analysis was subsequently conducted to reduce the dimension of multivariate data to two or three principal components, which can be visualized graphically with the least information loss. We used r software to calculate and visualize the principal component analysis (25). Probes without a corresponding gene symbol were then filtered and the average value of gene symbols with multiple probes was calculated using R software (26).…”
Section: Identification Of Differentially Expressed Genes (Degs)mentioning
confidence: 99%